Comparative study of bioethanol transformation catalyzed by Ru or Pt nanoparticles supported on KL zeolite. Issue 2 (4th September 2015) - Almohalla, M.; Gallegos-Suarez, E.; Arcoya, A.; Rodríguez-Ramos, I.; Guerrero-Ruiz, A.
Abstract : The catalytic properties of two noble metals, Pt and Ru, supported on KL zeolite were investigated in the selective transformation of bioethanol. Abstract : The catalytic properties of two noble metals, Pt and Ru, supported on KL zeolite were investigated in the selective transformation of bioethanol. In aiming to have an increased basicity of the catalyst, a KL zeolite modified by the addition of Ba was also used as support for Pt catalyst. For comparative purposes, Ru supported on hydrophobic high surface area graphite (HSAG) was also prepared. The catalytic tests were conducted in a fixed bed flow reactor, by feeding either pure ethanol vapor or a mixture of 10% water/90% ethanol in an inert gas, and working at low conversions to assure kinetic conditions. All the catalysts have relatively stable catalytic performance at up to 6 hours on stream with both reactant feedings. In general, the catalytic activities of Pt-based catalysts, given as turn-over-frequencies, were one order of magnitude higher than those obtained over Ru catalysts. It was also demonstrated that the nature of the supported metal nanoparticles (Ru vs. Pt) significantly affects the product selectivities. So when comparing Pt/KL and Ru/KL, methane and carbon monoxide by-products are mainly produced on the former, indicating that degradation of the primary product acetaldehyde by decarbonylation is higher on Pt catalysts. In the case of ruthenium nanoparticles, acetaldehyde is the predominant product. Finally, the comparison of Ru supported on KL zeolite and on HSAG revealed that, in the second case, ethylene is the principal by-product and that in some extension, this ethylene can be hydrogenated to ethane, probably spending hydrogen generated in the acetaldehyde formation. DRIFTS experiments were also conducted to identify the adsorbed intermediate species present under the reaction conditions on the different catalysts. All the selectivity differences have been rationalized using appropriate reaction pathways, and it is inferred that the variation of the chosen metal–support system is decisive to obtain a given reaction product.